Zoo and Wildlife Libraries: An International Survey. - Coates, Linda L.; Tierney, Kaitlyn Rose (Issues in Science and Technology Librarianship, 2010)
The conservation and well-being of exotic animals is core to the mission of zoos, aquariums and many small nonprofit wildlife groups. Increasingly, these organizations are committed to scientific research, both basic and applied. To ascertain the current state of the libraries that support their efforts, librarians at the San Diego Zoo conducted an international survey between June and August, 2008. Only 73 libraries responded to our request for information. Of that number only 16 libraries had professional librarians. Most are struggling to become more "virtual," but only 11 are OCLC members and have a catalog available online. Almost all libraries are involved in activities other than managing books and journals. They are creating animal fact sheets, maintaining staff article databases, and managing archival collections. For a complete picture of the current status of Zoo and Wildlife Libraries, see http://library.sandiegozoo.org/survey.htm [ABSTRACT FROM AUTHOR]